Experiences of childhood adversity across generations – Continuity or change? A study from the Northern Ireland youth wellbeing survey. (May 2022) - Bunting, Lisa; McCartan, Claire; Davidson, Gavin; Grant, Anne; Mulholland, Ciaran; Schubotz, Dirk; McBride, Orla; Murphy, Jamie; Nolan, Emma; Shevlin, Mark
Abstract: Background: Although a wealth of international literature consistently links cumulative experiences of adverse childhood experiences (ACEs) with physical, mental and emotional problems in later life, only a few studies have focused on intergenerational ACE exposure and research using nationally representative populations is lacking. Objective: This paper examines intergenerational associations between parent and child ACE scores in a large nationally representative sample of parent-child dyads. Participants and setting: Participant comprise 1042 pairs of parents and young people (11–19 year olds) who both completed questions relating to their exposure to ACEs ( N = 1042) as part the Northern Ireland Youth Wellbeing Survey (NIYWS) - a stratified random probability household survey of the prevalence of mental health disorders among 2 to 19 year olds in Northern Ireland ( N = 3074). Methods: Hierarchical regression was used to identify the relationship between parent and young people ACE scores and investigate the extent to which this is influenced by child, parent, family and socio-economic variables. Results: In the final model, young person ACE scores were associated with older child age (β = 0.082, p = .016), younger parental age (β = −0.083, p = .022), fewer children in the household (β = −0.120, p < .001), poor child health (β = 0.160, p < .001), low family support (β = 0.118, p = .001) and the household being in receipt of benefits (β = 0.223, p < .001). Conclusions: This study found a small association between parent and young person ACE exposure which was attenuated through other variables.